If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) + -1y + 4y = -1 Reorder the terms: 2(-3 + y) + -1y + 4y = -1 (-3 * 2 + y * 2) + -1y + 4y = -1 (-6 + 2y) + -1y + 4y = -1 Combine like terms: 2y + -1y = 1y -6 + 1y + 4y = -1 Combine like terms: 1y + 4y = 5y -6 + 5y = -1 Solving -6 + 5y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5y = -1 + 6 Combine like terms: -6 + 6 = 0 0 + 5y = -1 + 6 5y = -1 + 6 Combine like terms: -1 + 6 = 5 5y = 5 Divide each side by '5'. y = 1 Simplifying y = 1
| 7(-9x-7)=8x | | -10(s+1)=28 | | 3(6-4m)=2(9-6m) | | 8h+1=6h+19 | | 3(5-5x)=7(5-5x) | | 3-x^3=3x-4 | | 1x+9=2x-7 | | 2(5g-5)=3(5g-10) | | -6x+53=5 | | 14y-5=7(2y-2) | | -6+53=5 | | -8x+23=103 | | -3x-14x=85 | | 3h=6h+6 | | 3x*30=180 | | (4x-5)(x-2)= | | 4t-3=13+4t | | 4(3s+4)=76 | | 9x-5y=113 | | 0=12x-12 | | -164=-50x+36 | | 25+7a=27-4a | | -8x-11=45 | | 86=10x+26 | | (4r+2g)*(4r-2g)= | | 11+5x=-9 | | -18x-36=-36 | | f(x)=x^2+10x-3 | | x(x+1)-y(y+1)=0 | | 11x-16=-49 | | 2x^2-(2x/2)=12 | | 38=3x+17 |